Հայ Միջնադարյան խճանկարչության քրիստոնեական ավանդույթը - Գրիգորյան, Սյուզաննա
Our knowledge of the mosaic art of Armenia would be quite limited, if the Armenian mosaics in Jerusalem were not preserved. According to written sources, in the V–VII centuries there were many Armenian monasteries and churches in the Holy City. Their existence and luxury has also been proved by the Armenian mosaics discovered during construction works in Jerusalem in the late 19th century. In terms of composition, motifs, and, partly, style, the Armenian mosaics both in Armenia and Jerusalem have noticeably retained antique features but at the same time have clearly moved away from them, acquiring new forms and contents in accordance with the ideological and artistic requirements of the era. Наши представления о мозаичной живописи Армении оказались бы совершенно ничтожными, если бы не сохранились армянские мозаики в Иерусалиме. По сведениям письменных источников, в Святом городе в V—VII вв. было множество армянских церквей и обителей. Судя по обнаруженным в армянских сооружениях Иерусалима образцам, мозаичная живопись имела широкое распространение. Армянские мозаики как в самой Армении, так и в Иерусалиме по композиции, мотивам, отчасти и стилистическим особенностям заметно сохраняют черты мозаичной живописи античного периода, но в то же время явно отошли от них, приобретая новые формы и содержание в соответствии с идеологическими и художественными требованиями эпохи.
Keywords: Խճանկարչություն; Քրիստոնեություն; Միջնադարյան արվեստ